2000
DOI: 10.1051/gse:2000108
|View full text |Cite
|
Sign up to set email alerts
|

Expression of common fragile sites in two Ceboidea species: Saimiri boliviensis and Alouatta caraya (Primates: Platyrrhini)

Abstract: Fragile sites are points of preferential breakage that may be involved in chromosome rearrangements. Induction of common fragile sites (c-fra) and spontaneous breakage were analyzed in two New World Monkeys species: Saimiri boliviensis (SBO) and Alouatta caraya (ACA). Spontaneous chromosome aberrations were analyzed on untreated lymphocyte cultures with Brögger's formula (1977). SBO presented a low level of spontaneous breakage, while higher frequencies were detected in ACA in which bands 1q23; 2q13 and 11q19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Also it has been proposed that interbands between heterochromatic and euchromatic regions may be more susceptible to breakage. On the contrary, Fundia et al [4], found no significant correlation between heterochromatic regions or structural changes and fragile sites, in two New World Monkey species.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also it has been proposed that interbands between heterochromatic and euchromatic regions may be more susceptible to breakage. On the contrary, Fundia et al [4], found no significant correlation between heterochromatic regions or structural changes and fragile sites, in two New World Monkey species.…”
Section: Introductionmentioning
confidence: 98%
“…APC is a diterpenoid mycotoxin, which specifically inhibits eukaryotic DNA polymerase alpha and beta [15]. APC induced fragile sites are well documented in humans but have been studied only sporadically in mammals and domestic animals, mainly in primates, pigs, cats, and cattle [4,6,9,12].…”
Section: Introductionmentioning
confidence: 99%
“…Induction of fragile sites was also described in gorilla, chimpanzee and orangutan, showing an evolutionary conservation of these sites between the Great Apes and man and suggesting that fragile sites have been highly conserved during primate evolution [58,60,70]. In order to analyze the conservation of fragile sites in Ceboidea, the present data were compared to previous results on Cebus apella paraguayanus (CAP) chromosomes identifying 11 induced fragile sites (2q13, 2q26, 3q31, 5q22, 6q21, 11q15, 12q22, 19q13, 19q22, 20q13 and Xq22) [22,46]. Taking into account the chromosome homologies previously described in SBO, ACA and CAP [43], a homologous c-fra at band Xq22 was observed in all three species.…”
Section: Discussionmentioning
confidence: 99%
“…Since these six aberrations were located on different bands, no bands significantly involved in spontaneous breakage were found in SBO. On the other hand, spontaneous breakage analysis in ACA considering a haploid karyotype of 287 bands [21,22,46,47] demonstrated that any band with 2 or more lesions was non-randomly damaged (p < 0.01), identifying 3 bands: 1q23, 2q13 and 11q19 which were hot-spots for spontaneous breakage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation